KESALAHAN PENGGUNAAN EJAAN DAN TANDA BACA DALAM PENULISAN KARYA TULIS ILMIAH MAHASISWA DI PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS LAMPUNG - Wibowo, Duta Inovasi; Munandar, Muhammad Rafi; Riadi, Bambang; Prayogi, Rahmat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to describe the forms and types of spelling and punctuation errors found in the academic papers of students in the Indonesian Language and Literature Education Study Program at the University of Lampung. The research employed a qualitative descriptive approach with documentation as the data collection method. The data consisted of spelling and punctuation errors identified in 20 first-semester students’ papers during the 2024/2025 academic year. The findings revealed 125 errors, consisting of errors in the use of capital letters (30.4%), prepositions “di” and “ke” (21.6%), compound word writing (9.6%), commas (23.2%), and periods and quotation marks (15.2%). The most frequent errors were in the use of capital letters and commas. These mistakes occurred mainly due to students’ lack of understanding of the Pedoman Umum Ejaan Bahasa Indonesia (PUEBI), the influence of informal writing habits, and limited experience in editing academic texts. The results of this study are expected to serve as evaluation material for improving students’ academic writing skills, particularly in mastering the correct use of spelling and punctuation in higher education contexts.